Serangga yang Ditemukan Pada Beberapa Gulma di Sekitar Pertanaman Jeruk (Citrus sp.) di Kecamatan Ogan Komering Ilir, Sumatera Selatan - Irsan, Chandra; Anggraini, Erise; Riana, Nanda; Mawarni, Aprilliyah; Setiawan, Irenius Tegar; Harun, M. Umar (Seminar Nasional Lahan Suboptimal, 2023)
Irsan C, Anggraini E, Riana N, Mawarni A, Setiawan I.T., Harun, M.U. 2023. Insects found in some weeds around citrus (Citrus sp.) plantations in Ogan Komering Ilir Regency, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 742-748). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Citrus plants (Citrus sp.) are horticultural crops, and fruit commodities from the Rutaceae family. The presence of weeds around citrus plants provides an alternative host for other insects and attracts natural enemies of citrus pests. This research was conducted to find out what insects were found in weeds around citrus plants in Ogan Komering Ilir Regency, South Sumatra, Indonesia. The sampling method used in this research was the purposive sampling method. Observations were carried out from June to October 2023 in Ogan Komering Ilir Regency, South Sumatra, Indonesia. The results of observations showed that in the weeds around the citrus plants, 4 species of insects were found belonging to 3 families and 3 orders. The 4 species are Monomorium minimum, Oecophylla smaragdina, Dysdercus cingulatus, Oxya sp. The most frequently found species was M. minimum from the Formicidae family with a total of 846 individuals and the fewest are Oxya sp. (Orthoptera: Acrididae) with 6 individuals.